Developmental Cognitive Science Goes to School. - Stein, Nancy L. (Taylor and Francis, 2013)
This book addresses core issues related to school learning and the use of developmental/cognitive science models to improve school-based instruction. The contributors comprise a veritable ""who's who"" of leading researchers and scientists who are broadly trained in developmental psychology, cognitive science, economics, sociology, statistics, and physical science, and who are using basic learning theories from their respective disciplines to create better learning environments in school settings. Developmental Cognitive Science Goes to School:presents evidence.